Drive-amplitude-modulation atomic force microscopy: From vacuum to liquids - Jaafar, Miriam; Martínez-Martín, David; Cuenca, Mariano; Melcher, John; Raman, Arvind; Gómez-Herrero, Julio (Beilstein Journal of Nanotechnology, 2012)
We introduce drive-amplitude-modulation atomic force microscopy as a dynamic mode with outstanding performance in all environments from vacuum to liquids. As with frequency modulation, the new mode follows a feedback scheme with two nested loops: The first keeps the cantilever oscillation amplitude constant by regulating the driving force, and the second uses the driving force as the feedback variable for topography. Additionally, a phase-locked loop can be used as a parallel feedback allowing separation of the conservative and nonconservative interactions. We describe the basis of this mode and present some examples of its performance in three different environments. Drive-amplutide modulation is a very stable, intuitive and easy to use mode that is free of the feedback instability associated with the noncontact-to-contact transition that occurs in the frequency-modulation mode.
Keywords: atomic force microscopy; control systems; dissipation; frequency modulation; noncontact